2015
DOI: 10.1080/19439342.2015.1034156
|View full text |Cite
|
Sign up to set email alerts
|

The growth of impact evaluation for international development: how much have we learned?

Abstract: This article examines the content of a web-based repository of published impact evaluations of international development interventions. To populate this repository, we conducted a systematic search and screening process. We find that of the 2259 studies published from 1981 to 2012, annual publication increased dramatically after 2008. Most studies are on health, education, social protection and agriculture and are concentrated in South Asia, East Africa, South and Central America and Southeast Asia. There are … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
82
0
3

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 95 publications
(85 citation statements)
references
References 2 publications
0
82
0
3
Order By: Relevance
“…This is better than the mean lag for socialscience impact evaluations generally (see Cameron et al 2016), but our sample includes draft papers, while the population in the Cameron et al study does not. The right-hand side of the evidence gap map captures what we call other considerations, which are certain features of impact evaluations that help us to understand the evidence base.…”
Section: Resultsmentioning
confidence: 99%
“…This is better than the mean lag for socialscience impact evaluations generally (see Cameron et al 2016), but our sample includes draft papers, while the population in the Cameron et al study does not. The right-hand side of the evidence gap map captures what we call other considerations, which are certain features of impact evaluations that help us to understand the evidence base.…”
Section: Resultsmentioning
confidence: 99%
“…Much progress has been made towards the conceptualisation of the rationale for development effectiveness resulting in an increased supply of evidence such as impact evaluations and systematic reviews (Cameron, Mishra, and Brown 2015). The current state of the art in evidence-informed development then seems to meet Step 1 and Step 2 in the theory of change presented in Figure 1.…”
Section: Towards a Programme Theory Of Evidence-informed Developmentmentioning
confidence: 99%
“…Researchers at 3ie have compiled the most complete database of published impact evaluations available and found that as recently as 1995, fewer than 10 studies of developing country policies were published each year (see Figure 1). That number has grown rapidly, with more than 300 studies coming out annually (Cameron, Mishra, and Brown 2015). The Abdul Jameel Latif Poverty Action Lab (JPAL) and Innovations for Poverty Action (IPA) are relatively new research centres dedicated to conducting impact evaluations, and in 2014 they listed 567 and 220 ongoing studies, respectively.…”
Section: Politics Rules But Evaluation Still Holds Much Promisementioning
confidence: 99%